Dowry-Related Aggression and Mental Health Concomitants among Educated Women in Pakistan - Taalia Khan; Karin Österman; Kaj Björkqvist (Journal of Educational, Health and Community Psychology, 2020)
Abstract The aim of the study was to investigate victimization from dowry-related aggression and mental health concomitants in a sample of educated women in Pakistan. A questionnaire was completed by 569 women. The mean age was 31.4 years (SD 9.1). The questionnaire included two scales for measuring dowry-related aggression and four scales for measuring mental health concomitants.  The levels of victimization from dowry-related aggression were relatively low in the sample. Aggression carried out by the husband and the mother-in-law correlated highly with each other. The most common single act by both husbands and mothers-in-law was forcing the wife to give her gold to her mother-in-law or sister-in-law. Women who were more than average victimised from dowry-related aggression had significantly higher scores on anxiety, depression, obsessive-compulsive symptoms, and somatisation. Aggression carried out by the mother-in-law showed higher predictive power on all four mental health concomitants than aggression by the husband. Somatic symptoms of the daughter-in-law showed the highest association with aggression carried out by the mother-in-law. Victimization from dowry-related aggression was strongly associated with negative mental health outcomes. Aggression carried out by the mother-in-law was more strongly associated with them than aggression carried out by the husband.